Clumpiness of observed and simulated cold circumgalactic gas. Issue 4 (12th June 2021) - Augustin, Ramona; Péroux, Céline; Hamanowicz, Aleksandra; Kulkarni, Varsha; Rahmani, Hadi; Zanella, Anita
ABSTRACT: Determining the clumpiness of matter around galaxies is pivotal to a full understanding of the spatially inhomogeneous, multiphase gas in the circumgalactic medium (CGM). We combine high spatially resolved 3D observations with hydrodynamical cosmological simulations to measure the cold circumgalactic gas clumpiness. We present new adaptive-optics-assisted VLT/MUSE observations of a quadruply lensed quasar, targeting the CGM of 2 foreground z  ∼ 1 galaxies observed in absorption. We additionally use zoom-in FOGGIE simulations with exquisite resolution (∼0.1 kpc scales) in the CGM of galaxies to compute the physical properties of cold gas traced by Mg ii absorbers. By contrasting these mock-observables with the VLT/MUSE observations, we find a large spread of fractional variations of Mg ii equivalent widths with physical separation, both in observations and simulations. The simulations indicate a dependence of the Mg ii coherence length on the underlying gas morphology (filaments versus clumps). The z abs  = 1.168 Mg ii system shows coherence over ≳6 kpc and is associated with an [O ii ] emitting galaxy situated 89 kpc away, with SFR ≥ 4.6 ± 1.5 $\rm M_{\odot }$  yr −1 and M * = 10 9.6 ± 0.2 M⊙ . Based on this combined analysis, we determine that the absorber is consistent with being an inflowing filament. The z abs  = 1.393 Mg ii system traces dense CGM gas clumps varying in strength over ≲2 kpc physical scales. Our findings suggest that this absorber is likely related to an outflowing clump. Our joint approach combining 3D-spectroscopy observations of lensed systems and simulations with extreme resolution in the CGM put new constraints on the clumpiness of cold CGM gas, a key diagnostic of the baryon cycle.